Assessment of the Burala Canal Irrigation System, Pakistan : an application of the MASSCOTE approach - Nabi, Abdul; Babel, Mukand Singh; Perret, Sylvain Roger; Clemente, Roberto S.; Sutat Weesakul; The Netherlands (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
Irrigated agricultural plays an important role in the economy of Pakistan. Agriculture in Pakistan is fed by surface canal irrigation system and mostly the performance of canal irrigation system is poor. The overall objective of this study was to apply the MASSCOTE (Mapping System and Services for Canal Operation Techniques) approach for the modernization of an irrigation system in Pakistan to improve its performance. Burala Canal Irrigation System located in the Rechna Doab, Punjab province was selected for the study. Various steps of MASSCOTE approach were applied to meet the objectives of the study. The current performance was evaluated, weaknesses in the system were identified and then modernization actions were specified to improve the performance of the system. The analysis showed that the values of most of the internal indicators, like water delivery service, operation of the canal etc. were below average showing poor performance of the system. Among the various external indicators, cost recovery ratio of the system was about 45 percent and maintenance cost to revenue ratio was 0.47. The operational and maintenance expenditures were higher than the water charges collected/ assessed in the study area. The water fees collection had declined over the years. The staff salaries shared the maximum portion of the expenditures. The study found that water provided from the main canal to distributaries was quite equitable but large scale inequity existed at the minor canal levels. The water theft and tempered outlets were the main reasons of poor water delivery services. The analysis indicated that most of the offtake delivery structures were highly sensitive and their sensitivity increased with the decrease of head upstream side of the structure and vice versa. The structures with high sensitivity need to be operated more efficiently for better services
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2008
Keywords: Irrigation projects -- Evaluation -- Pakistan